Exploring ESG Corporate Tax Honesty Behind Ownership Structure and Financial Constraints - Agustina R Pangaribuan; Dielanova Wynni Yuanita (Journal of Accounting, Business and Management (JABM), 2026)
The purpose of this research is to determine which ownership structure, for the years 2019-2023, has the greatest impact on tax evasion by ESG-indexed businesses. This study uses quantitative methodology with purposive sampling as the sampling technique. Ownership structure is measured through three categories: concentrated ownership structure, family ownership structure, and the presence of women on the board of directors. In addition, financial constraints are used to examine tax avoidance. ESG Score is used as a moderating variable and only taken from the last year of observation to explain the impact of ownership structure and financial constraints on tax savings. When faced with financial constraints, ESG-indexed enterprises with concentrated ownership structures, family ownership structures, and the participation of women on the board of directors did not affect tax-saving strategies, according to the study findings. ESG-indexed corporations fulfill environmental, social, and governance obligations to uphold public and investor confidence. The ownership structure and financial restrictions are not metrics that can ascertain whether a corporation engages in tax-saving strategies.